"Other languages, other landscapes, other stories": Reading Resurgence in the Contemporary Indigenous Novel - Evans, Vanessa Kimberley (2023)
As settler and postcolonial countries in North America, Oceania, and South Asia contend with the complexity of reconciliation, sovereignty movements, and the fallout from colonial schools, the relevance of Indigenous resurgence is rising on a global scale. This resurgence responds, in part, to the specific role literature can and has played in disconnecting Indigenous Peoples from their knowledges, communities, and selves. Accordingly, in this dissertation I make connections between seemingly disparate Indigenous novels in an effort at beginning to understand what representations of resurgence—the everyday practices and processes that seek to regenerate and rebuild Indigenous nations—reveal about how diverse Indigenous contexts are (re)imagining Indigenous worlds and what connections across those contexts might mean (Simpson 2017). To perform this investigation, I make a case for further cross-cultural comparative methods within Indigenous literary studies that can interpret resurgence across distinct literary contexts while maintaining a commitment to nation-specific worldviews imparted by relation with land. Mobilizing the theoretical work of Leanne Betasamosake Simpson (Michi Saagiig Nishnaabeg), Chadwick Allen, and Molly McGlennen (Anishinaabe), this project contributes a new comparative method called reading resurgence. Located at the intersection of global and nationalist approaches to Indigenous literary studies, this method interprets everyday acts of resurgence—specifically: storytelling, language learning, and relationship with land—trans-Indigenously across three respective literary constellations of coresistance that cluster novels from diverse Indigenous nations. The first constellation reads resurgence across David Treuer’s (Leech Lake Ojibwe) The Translation of Dr Apelles (2006), Patricia Grace’s (Māori) Potiki (1986), and Rejina Marandi’s (Santal) Becoming Me (2014). The second clusters Cherie Dimaline’s (Métis) The Marrow Thieves (2017), Sia Figiel’s (Samoan) Where We Once Belonged (1996), and ...